Answer:
f(-6) = 72
Explanation:
We are given the function f(x)=2x², and want to find the value of f(-6).
Finding f(-6) means that we want to evaluate the function for when x is equal to -6. In other words, we need to substitute -6 as x (in 2x^2).
So, substitute -6 as x.
f(-6)=2(-6)²
Now, we must follow the order of operations here (PEMDAS, or any other similar abbreviation, depending on your location), meaning that we should take care of the exponent first.
So, raise -6 to the 2nd power (ignore the 2 in front of (-6)² for now).
f(-6)=2(-6)² = -6 * -6 = 36
Now multiply 36 by 2.
f(6) = 2 * 36 = 72
That means f(-6) = 72.